2020
DOI: 10.1039/c9ra08707a
|View full text |Cite|
|
Sign up to set email alerts
|

Boron-doped few-layer graphene nanosheet gas sensor for enhanced ammonia sensing at room temperature

Abstract: A boron-doped few-layer LPCVD graphene sensor is successfully designed and demonstrated for enhanced NH3 gas sensing applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 75 publications
2
34
0
2
Order By: Relevance
“…Foreign dopant atoms can alter the properties of graphene. Hence, doping has further opened the door to many graphene-based applications including electronics [38] and sensing [39] owing to the distinct nature of each dopant. [40,41] These impurity atoms display unique bonding configurations in the graphene lattice (see Figure 1i), endowing the graphene with distinctive properties.…”
Section: Bonding Configurationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Foreign dopant atoms can alter the properties of graphene. Hence, doping has further opened the door to many graphene-based applications including electronics [38] and sensing [39] owing to the distinct nature of each dopant. [40,41] These impurity atoms display unique bonding configurations in the graphene lattice (see Figure 1i), endowing the graphene with distinctive properties.…”
Section: Bonding Configurationsmentioning
confidence: 99%
“…For highly sensitive sensors of ammonia, Srivastava et al found that B-doped graphene exhibited speedy response (high sensitivity) to ammonia and immediate recovery. [39] The determination of hydrogen peroxide (H 2 O 2 ) has significance in both the industry and biological reactions. Zhang et al proposed a composite system (Co 3 O 4 decorated N-doped graphene) for fast, accurate, and reliable detection of H 2 O 2 .…”
Section: Sensing Of Gas and Dyesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results obtained indicated a new strategy to construct handy and quick gas sensing devices based on BFLGr. 51 2.1.4 Biosensors. Mannan et al synthesized GO using a modied Hummers method and successful boron doping (1.64-1.83%) was executed with boric acid as a precursor by hydrothermal reaction.…”
Section: Boron-doped Graphene (Bg)-based Sensorsmentioning
confidence: 99%